PENERAPAN TEKNOLOGI DAN KONSTRUKTIVISME DALAM PENDIDIKAN TATA BUSANA - Yenni Idrus (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
Technology in this our world is always growing rapidly. Technology can be used as an indicator that shows enhancement in a sector. In the education sector, advanced technology influences the way we teach and the way we learn. Fashion education also cannot avoid the influence of technology. Teachers and learners in Fashion education ideally should utilize the technology in their learning process. Technology has a close relationship with constructivism. Both technology and constructivism is equally lead people in constructing their own knowledge independently. This article is intended to describe briefly and clearly about the definition of Fashion education, the definition of constructivism, as well as the application of technology and constructivism in Fashion education.